2016
DOI: 10.1038/srep19251
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced alternative transcription and splicing events and their applicability to practical biodosimetry

Abstract: Accurate assessment of the individual exposure dose based on easily accessible samples (e.g. blood) immediately following a radiological accident is crucial. We aimed at developing a robust transcription-based signature for biodosimetry from human peripheral blood mononuclear cells irradiated with different doses of X-rays (0.1 and 1.0 Gy) at a dose rate of 0.26 Gy/min. Genome-wide radiation-induced changes in mRNA expression were evaluated at both gene and exon level. Using exon-specific qRT-PCR, we confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 47 publications
5
61
0
Order By: Relevance
“…Dose assessment in irradiated blood samples can be obtained by either using dose predictive gene or exon signatures (Paul & Amundson 2008;Kabacik et al 2011;Boldt et al 2012;Knops et al 2012;Lucas et al 2014;Macaeva et al 2016) or by monitoring the modification of transcription of single radiation-responsive genes like ferredoxin reductase (FDXR) (Manning et al 2013;Abend et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dose assessment in irradiated blood samples can be obtained by either using dose predictive gene or exon signatures (Paul & Amundson 2008;Kabacik et al 2011;Boldt et al 2012;Knops et al 2012;Lucas et al 2014;Macaeva et al 2016) or by monitoring the modification of transcription of single radiation-responsive genes like ferredoxin reductase (FDXR) (Manning et al 2013;Abend et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In ex vivo studies, several protocols have been used such as cultured peripheral blood mononuclear cells (PBMC) (Dressman et al 2007;Meadows et al 2008Meadows et al , 2010Sprung et al 2011;Boldt et al 2012;Knops et al 2012;Riecke et al 2012;Macaeva et al 2016), cultured whole blood diluted with media Brzoska andKruszewski 2015, Abend et al 2016) or undiluted whole blood (Manning et al 2013). However, none of these studies have addressed the role of blood culture methods during the incubation time at 37 C following radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this approach is time consuming and highly technique dependent, and detection of very low or high dose is limited. Because of these limitations, studies published over the past several years have suggested the development of gene expression profiles in biological fluid, especially in blood, as an alternative approach for identifying exposed individuals and assessing absorbed dose (28). These studies have shown promising results indicating that distinctive gene expression patterns could be highly correlated with different radiation doses.…”
Section: Introductionmentioning
confidence: 99%